Temperature Effect on Al/p-CuInS2/SnO2(F) Schottky Diodes - Ben Nasrallah, T.; Mahboub, D.; Jemai, M.; Belgacem, S. (Engineering, Technology & Applied Science Research, 2019)
In this paper, Schottky diodes (SDs) obtained by evaporated thin films of aluminum on pulverized p-CuInS2/SnO2:F have been studied using J-V-T characteristics in a temperature range of 200-340K. These characteristics show that aluminum acts as a rectifier metal-semiconductor contact. Characteristic variables of the Al/p-CuInS2/SnO2:F junctions, such as the current density, the serial resistance, the parallel conductance, the Schottky barrier height (SBH), and the ideality factor of the SD were obtained by fitting the J-V-T data using the Lambert function. Data analysis was conducted with the use of MATLAB. Results showed that n is greater than 1, which could be explained by the existence of inhomogeneities due to the grain boundaries in CuInS2. Through this analysis, one can see a good agreement between experimental and modeled data. The study has shown that the main contribution in the current conduction in such heterostructures is the thermionic emission (TE) supported by the recombination of the carriers. The last phenomenon appears mainly in the grain boundaries, which contain both intrinsic and extrinsic defects (secondary phases, segregated oxygen). An investigation of the J-V-T characteristics according to TE theory has demonstrated that the current density and the SBH increase while serial resistance, parallel conductance decrease with an increase in temperature. After an SBH inhomogeneity correction, the modified Richardson constant and the mean barrier height were found to be 120AK-2cm-2 and 1.29eV respectively. This kind of behavior has been observed in many metal-semiconductor contacts.